2021
DOI: 10.1002/hbm.25377
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance accounts for metabolic syndrome‐related alterations in brain structure

Abstract: Metabolic syndrome (MetS) is a major public health burden worldwide and associated with brain abnormalities. Although insulin resistance is considered a pivotal feature of MetS, its role in the pathogenesis of MetS-related brain alterations in the general population is unclear. Therefore, in 973 participants (mean age 52.5 years) of the population-based Rhineland Study, we assessed brain morphology in relation to MetS and insulin resistance, and evaluated to what extent the pattern of structural brain changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 51 publications
1
25
0
1
Order By: Relevance
“…Previous studies reported the association between insulin resistance and cSVD using the homeostatic model assessment for insulin resistance (HOMA-IR), with mixed results. [4][5][6][7] As HOMA-IR is based on fasting glucose and fasting insulin, the accuracy in reflecting insulin sensitivity might be limited. The insulin sensitivity index (ISI 0,120 ) defined by Gutt et al, based on postglucose load measures, shows a better correlation with hyperinsulinemic-euglycemic clamp than HOMA-IR, and reflects both peripheral and hepatic insulin sensitivity.…”
Section: Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported the association between insulin resistance and cSVD using the homeostatic model assessment for insulin resistance (HOMA-IR), with mixed results. [4][5][6][7] As HOMA-IR is based on fasting glucose and fasting insulin, the accuracy in reflecting insulin sensitivity might be limited. The insulin sensitivity index (ISI 0,120 ) defined by Gutt et al, based on postglucose load measures, shows a better correlation with hyperinsulinemic-euglycemic clamp than HOMA-IR, and reflects both peripheral and hepatic insulin sensitivity.…”
Section: Metabolismmentioning
confidence: 99%
“…Increasing amount of evidence showed that insulin resistance was associated with increased risk of macrovascular and microvascular complications even in patients without diabetes. Previous studies reported the association between insulin resistance and cSVD using the homeostatic model assessment for insulin resistance (HOMA-IR), with mixed results 4–7. As HOMA-IR is based on fasting glucose and fasting insulin, the accuracy in reflecting insulin sensitivity might be limited.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of the hypothalamic–pituitary–adrenal (HPA) axis responding to insomnia and proinflammatory cytokines could lead to the level of sleep efficiency and objective sleepiness [ 45 ]. In addition, insulin resistance sensitivity might be decreased by sleep restriction or sleep fragmentation [ 46 ], which play a crucial role in the prevention of MetS-related brain changes [ 47 ]. Our stratified analysis reveals that differences in the relationship of sleep duration and MetS components between the participants with or without MetS, indicating that insomnia symptoms significantly influence the relationship between sleep duration and MetS components.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that insulin resistance may impact several insulin-sensitive brain circuitries involved in eating behavior such as prefrontal regions [ 39 , 40 ]. For instance, recent neuroanatomical studies with large sample size also showed that insulin resistance is associated with lower cortical thickness in frontoparietal and temporal brain regions [ 67 , 68 ]. Other studies also showed to the chronic, low-grade inflammation related to obesity as a potential mechanism explaining obesity-induced grey matter alterations [ 69 ].…”
Section: Discussionmentioning
confidence: 99%